Military-political Processes in the Caucasus Region and the Security of Russia - A. V. Vilovatykh (MGIMO University Press, 2015)
The unipolar world breaking and the tightening of geopolitical struggle led to destructive military-political processes in different regions of the world. In conditions of instability along the perimeter of Russia's borders the significance of the Caucasus region increases, especially in geo-strategic and geoeconomic perspectives. The efforts of world politics actors for the transformation of the region environment increase substantially. As a result the dynamics and the scope of the proceeding military-political processes in the Caucasus are complicated. The failures in the assessment and the prediction of the processes development influence on the safety of Russia. Wrong gradation of existing threats and challenges can lead to disastrous and irreversible consequences for state security. Designated circumstances caused the need for the expert survey on assessing the impact of the current military-political processes in the Caucasus region on the security of the Russian state and necessity for the concretization of military dangers and threats, due to political and military developments in the Caucasus. An expert survey was conducted in June 2014. During it authors interviewed 40 Russian and foreign experts representing Federal and regional authorities, academic community, research centers, analytical structures. Implementation of the survey allowed to identify the experts positions and the degree of their coherence on the military-political processes in the Caucasus region and their impact on the modern Russia security. As a result the degree of destructiveness of the regional military-political processes was fixed. We conclude that anti-Russian processes in the countries of the Caucasus continue to determine the overall geopolitical situation, including in the military-political sphere. The reason is mainly seen in interests clashing of Russia and countries of the "Atlantic world." Analysis of the military-political processes in the Caucasus region has allowed to formulate the main directions of improving the efficiency of Russian state policy in security sphere in the North Caucasus and in the States of South Caucasus.